A rare case of pulmonary nocardiosis comorbid with Sjogren's syndrome. Issue 9 (21st August 2021) - Peng, Yumeng; Dong, Xiaoyan; Zhu, Yongze; Lv, Huoyang; Ge, Yumei
Abstract: Background: Nocardia is an opportunistic pathogen, which occurs in patients with autoimmune diseases and immune dysfunction, and can cause bacteremia and other life‐threatening complications. The clinical manifestations of Nocardia pneumonia are similar to tuberculous and other clinical common bacterial pneumonia, but its antibacterial treatments are different and detection methods are unique, which may lead patients to suffer for many years due to clinical misdiagnosis and missed diagnosis. Methods: Imaging and laboratory examinations were performed for preliminary diagnosis, and next‐generation sequencing was used to identify the exact species type of Nocardia in the bronchoalveolar lavage fluid (BALF) of the patient. Results: Imaging and laboratory parameters preliminarily implied that the patient was infected with Nocardia with Sjogren's syndrome (SS), and NGS showed that the strain was N .  terpenica . Conclusions: Accurate etiological diagnosis and corresponding antibiotics are key to improve the prognosis of pulmonary nocardiosis in this case. Nocardia pneumonia is rare in clinical practice; it is of great medical significance to improve the understanding of pulmonary nocardiosis.